EXPLORING LECTURERS’ EXPERIENCES IN TEACHING WRITING SKILLS THROUGH ONLINE LEARNING AT THE ENGLISH LANGUAGE EDUCATION STUDY PROGRM OF KHAIRUN UNIVERSITY - Risnawati Taslim; Naniek Jusnita; Abdulhalim Daud; Ade Ismail (Cakrawala Bahasa, 2022)
The purpose of this research was to explore three lecturers of English Education Study Program experiences in teaching writing online, types of online learning platform, Techniques that used in teaching writing online, and the challenges faced by the lecturers. This research applied descriptive qualitative method and three lecturers participated as respondents of this research. Data were collected through interview and checklist questionnaire and the data were analyzed using content analysis. The results showed that in teaching writing online, the lecturers used a number of online learning platform where they have been familiar those online learning platform, such as Whatsapp messenger, Virtual class, Zoom meeting, and Google meet. Further, in terms of techniques in teaching writing, it is found that the lecturers use Picture technique, Reading technique, Teaching organization technique, Controlled writing technique, Mind mapping, and List techniques. It was also found in this research that there a number of challenges faced by the lecturers during teaching writing through online;(1) Lecturers got challenges to control students during writing their drafts. (2) it is sometime the lecturer get challenges of time management, it is take time to access the online learning platform and it is also some of the online platform should be paid monthly and the last, the lecturers has limited internet quality access.